A clinical approach to nightmares and bad dreams in cognitive–behavioural therapy. (May 2022) - Carona, Carlos; Fonseca, Ana
SUMMARY: Clinicians trained in cognitive–behavioural therapy (CBT) are frequently not trained to work with dreams. Given the high prevalence and impact of nightmares and bad dreams, empowering CBT therapists to effectively work with these sleep phenomena is crucial to improve therapeutic outcomes. This article briefly outlines a cognitive–behavioural model of dreams and reviews some clinical guidelines for directly and indirectly addressing nightmares and bad dreams in CBT practice.